On the Structure of the Beserman Dictionary Based on the Materials of T. I. Teplyashina - Sergey A. Maksimov (Publishing house "Sreda", 2022)
This work is devoted to description of the microstructure (dictionary entry) of the Beserman dictionary, which is compiled based on the materials of T. I. Teplyashina. Besermans are small people who live compactly in the North West of Udmurtia. From the point of view of linguistics they speak a special dialect of the Udmurt language. The Besermans have a stable ethnic and linguistic identity, which is different from the Udmurt. At the beginning of the 21st century, the language of Besermans has become an object of considerable interest for linguists. Field materials were embodied in two dictionaries, a monograph and scientific articles. The most significant contribution to the study of the Beserman dialect was made by T. I. Teplyashina, who published the monograph "The Language of the Besermans". Most of her materials, which were systematized in a field file, remained unused. The scientist's field file representing the Beserman speech of speakers born in the century before last can be called a unique linguistic heritage, waiting to be processed and implemented as a dictionary. Our dictionary will contain lexical and textual materials published in monographs and previously unpublished. This article examines in detail the structure of the dictionary, which has no analogues, at least in the lexicography of the Ural-Volga region.